Needs Analysis of Instructional Materials in the Contextual Teaching Course - GH, Muliana; Pratiwi, Andi Citra (PT Mattawang Mediatama Solution, 2025)
This study focuses on the importance of teaching materials in the lecture process, particularly in the contextual teaching course at Universitas Negeri Makassar. Using a qualitative descriptive approach, data were collected through observation and questionnaires. The subjects of this study were students enrolled in the contextual teaching course, consisting of 69 students. The results of the study indicate that the majority of students do not have textbooks as learning resources for the contextual teaching course; the learning resources they commonly use are sourced from the internet. The findings also reveal that the application of biological concepts in contextual teaching is still limited, with few examples of its implementation available. Based on the results, information was obtained regarding subtopics that are difficult to understand in the contextual teaching course, particularly in the subtopic of assessment in contextual learning within the psychomotor domain. On the other hand, material that students find easy to understand is the application of contextual teaching in direct instruction. The results also show that 98.6% of students agree on the need to develop a teaching module. The preferred form of the teaching module among students is both print and electronic versions. Therefore, the development of a comprehensive teaching module is considered necessary to support the learning process. This study is expected to serve as a basis for the development of more effective teaching materials to support contextual teaching lectures.